Clinical spectrum of infantile scimitar syndrome: A tertiary center experience - Hadeel Al Rukban; Mohammed Al Ghaihab; Omar Tamimi; Suhail Al-Saleh (Wolters Kluwer Medknow Publications, 2014)
Aim: Infantile scimitar syndrome is a rare condition, with most of the literature reports being limited to case reports and a few case series. The aim of this study was to review patients with infantile scimitar syndrome who presented to our hospital from July 2000 to January 2011. Materials and Methods: In this retrospective study, we evaluated the medical records of patients aged 0-14 years who were symptomatic before the age of 1 year and were subsequently diagnosed with the syndrome. A total of 16 patients with the infantile form of scimitar syndrome were identified from the database. Results: The median age at presentation was 14 days, with a median age at diagnosis of 55 days. Fifty-six percent of the patients were females. Tachypnea was the major presenting symptom and 13 out of 16 patients had pulmonary hypertension. Of the 13 patients with pulmonary hypertension, 7 had systemic collaterals, which were treated by coil occlusion together with medications, and 3 had corrective surgery. The mortality rate was 3/16 (18.8%) over the 10.5 years study period. Conclusions: Infantile scimitar syndrome is a rare congenital anomaly that needs a high degree of suspicion for early referral and management. The association of the syndrome with pulmonary hypertension leads to recurrent and prolonged hospitalization.